Perspectives from Public Relations :Media Relations in an Evolving Media Landscape - Putri Hartiana, Theresia Intan (Universitas Bunda Mulia, 2024)
The purpose of this research is to describe how Public Relations professionnals understands journalists and the media industry works to provide the information to maximise company publications in the media. This research was conducted with in-depth interviews with Public Relations professionals from different companies. Mediating The Media Model will help PR professionals understand the important factors in establishing media relations and media coverage, especially when social media and mainstream media intersect. Media relations extend beyond establishing communication with journalists. Media relations is a complex ,activity; by considering the media works, and the publication strategy that must be given to get news coverage. Especially with the development of digital technology, it provides a new space for Public Relations to carry out media relations.This research found that news values are the primary consideration in providing information subsidies to the media. Although company advertisers are considered as the primary determinant of newsrooms loading company news, the development of digital media has changed how Public Relations defines the meaning of media in media relations. Media is no longer limited to mainstream media, but also personal channels like in the case of influencers. Some mainstream media are also starting to be abandoned, particularly the radio and. online news is becoming the first choice. Public Relations realizes several factors that influence their company's media coverage.